Open versus minimally invasive total gastrectomy after neoadjuvant chemotherapy: results of a European randomized trial - Wielen, Nicole van der; Straatman, Jennifer; Daams, Freek; Rosati, Riccardo; Parise, Paolo; Weitz, Jürgen; Reißfelder, Christoph; Diez del Val, Ismael; Loureiro, Carlos; Parada-González, Purificación; Pintos-Martínez, Elena; Mateo Vallejo, Francisco; et al. (Gastric cancer, 2021)
Surgical resection with adequate lymphadenectomy is regarded the only curative option for gastric cancer. Regarding minimally invasive techniques, mainly Asian studies showed comparable oncological and short-term postoperative outcomes. The incidence of gastric cancer is lower in the Western population and patients often present with more advanced stages of disease. Therefore, the reproducibility of these Asian results in the Western population remains to be investigated.
Published online: 31 July 2020
Gesehen am 23.04.2021